2018
DOI: 10.1039/c8tc00263k
|View full text |Cite
|
Sign up to set email alerts
|

A general and mild route to highly dispersible anisotropic magnetic colloids for sensing weak magnetic fields

Abstract: A porous-silica-protected conversion method is developed to prepare highly dispersible anisotropic magnetic colloids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…It was found that the silica shell plays a vital role in the preparation of the Co‐PS@SiO 2 catalyst. First, it functioned as the protection layer to preserve the overall nanoarray structure during the conversion of Co(OH) y (CO 3 ) 0.5(2− y ) · n H 2 O into metallic Co. [ 12 ] In the absence of the silica shell, the nanoarray structure was fully collapsed after annealing (Figure S11, Supporting Information). Moreover, the silica shell provided the confined environment to limit the growth of Co nanocrystals.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the silica shell plays a vital role in the preparation of the Co‐PS@SiO 2 catalyst. First, it functioned as the protection layer to preserve the overall nanoarray structure during the conversion of Co(OH) y (CO 3 ) 0.5(2− y ) · n H 2 O into metallic Co. [ 12 ] In the absence of the silica shell, the nanoarray structure was fully collapsed after annealing (Figure S11, Supporting Information). Moreover, the silica shell provided the confined environment to limit the growth of Co nanocrystals.…”
Section: Figurementioning
confidence: 99%
“…Moreover, the silica shell provided the confined environment to limit the growth of Co nanocrystals. [ 12 ] This is evidenced from the increased Co grain size of 47 nm in Co/FTO (Figure S12, Supporting Information).…”
Section: Figurementioning
confidence: 99%
“… [10a,64] The Si–O–Si groups are usually inert in chemical reactions unless the defects are generated (e.g., ≡Si· and ≡SiO·), which were demonstrated to be active in methanation of CO 2 (Figure 7a). [64c] The hydrophilic Si–OH groups can make 2D Si well dispersed in water, benefiting photocatalytic reactions in aqueous solutions [64a,66] . Moreover, the active –OH groups could crosslink with many kinds of surfactants and functional groups so that 2D Si could be modified with abundant useful ligands (e.g., –NH 2 and –SH) as required.…”
Section: The Advantages and Perspectives Of 2d Silicon‐based Catalystsmentioning
confidence: 99%
“…Stöber method has been proven as an effective route to coat nanoparticles with silica shells. 40,41 The sol-gel process involves the hydrolysis and condensation of a silane precursor (e.g. tetraethyl orthosilicate).…”
Section: Resultsmentioning
confidence: 99%